The rise of transnational environmental law and the expertise of environmental lawyers - Fisher, E (2012)
The concept of transnational environmental law is used descriptively and prescriptively to refer to a multitude of legal processes which are distinct from transnational law in other legal areas. Hence, the rise of transnational environmental law requires environmental lawyers to reflect on their skills and knowledge and to foster both their contributory and interactional expertise in this area. That process of fostering expertise needs to be seen in light of a number of intellectual challenges, including the necessity to engage with comparative environmental law methodology, the need to not privilege one legal system over others, the need to engage with extended legal pluralism, the importance of thinking about the role of language in legal processes, and the significance of understanding the process of co-production. Copyright © Cambridge University Press 2011.